Point-of-Care Ultrasonography Findings and Care Use Among Patients Undergoing Ultrasound-Guided Shoulder Injections. (January 2018) - Lee, Se Won; Tiu, Timothy; Roberts, Jeremy; Lee, Brian; Bartels, Matthew N.; Oh-Park, Mooyeon
Abstract : Objective: The aims of the study were to assess the overall reduction of pain in patients undergoing ultrasound-guided shoulder injections and to characterize the preinjection point-of-care ultrasound findings and use of clinical services postinjection including the use of magnetic resonance imaging and surgeries. Design: Data of 172 patients who underwent ultrasound-guided subacromial subdeltoid injection or glenohumeral joint injection were reviewed for preinjection point-of-care ultrasound findings, change in pain intensity at 2 mos from baseline, and use of care at 6 mos' postinjection. Pain intensity was measured by the numeric rating scale and a dichotomous report of global impression of significant improvement in pain. Responders were defined as those with 50% or more reduction in numeric rating scale or those with global impression of 50% or more improvement. Results: There were 141 responders among the 172 patients analyzed. Full-thickness rotator cuff tears were higher in the ultrasound-guided subacromial subdeltoid injection group when compared with the glenohumeral joint injection group ( P = 0.038) and abnormal bicipital tendon findings higher in the glenohumeral joint injection group ( P = 0.016). There were no significant differences in specific abnormal U findings between responders versus nonresponders. Twelve patients had a shoulder magnetic resonance imaging and four patients underwent operative interventions after the injection. Conclusions: Overall pain reduction after ultrasound-guided shoulder injections was favorable in the short term. There was no specific preinjection point-of-care ultrasound findings associated with clinical pain reduction after injection. Additional imaging and operative intervention after ultrasound-guided shoulder injections seemed to be relatively low.